2002
DOI: 10.1080/00420980220112801
|View full text |Cite
|
Sign up to set email alerts
|

Urban Form and Travel Behaviour: Micro-level Household Attributes and Residential Context

Abstract: Many countries now have policies to reduce distances travelled by private car and to favour the use of public transport, cycling and walking. The development of compact urban forms and the design of urban communities which favour walking are seen as particularly effective strategies for reducing car dependency. The factors which determine travel behaviour are not fully understood, so that effective policies influencing travel patterns are difficult to formulate. Apart from urban form and design, personal attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
246
3
19

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 385 publications
(288 citation statements)
references
References 25 publications
20
246
3
19
Order By: Relevance
“…According to their analyses the built environment has a significant influence on non-work travel, whereas work travel is almost entirely determined by personal characteristics. Dieleman et al (2002) found an equal influence of the built environment and personal characteristics. On the other hand, several studies point out that the built environment has only a moderate effect on travel behaviour (e.g., Cervero and Kockelman, 1997;Schwanen et al, 2004;Simma and Axhausen, 2003;Stead, 2001).…”
Section: The Built Environment or The Individual And Its Household ?mentioning
confidence: 98%
See 3 more Smart Citations
“…According to their analyses the built environment has a significant influence on non-work travel, whereas work travel is almost entirely determined by personal characteristics. Dieleman et al (2002) found an equal influence of the built environment and personal characteristics. On the other hand, several studies point out that the built environment has only a moderate effect on travel behaviour (e.g., Cervero and Kockelman, 1997;Schwanen et al, 2004;Simma and Axhausen, 2003;Stead, 2001).…”
Section: The Built Environment or The Individual And Its Household ?mentioning
confidence: 98%
“…Hence, highly educated persons often obtain more specialized jobs which are generally concentrated in high-density or central business district office parks. As a result, higher educated are more involved in long-distance commuting and their car use is higher (Boarnet and Sarmiento, 1998;Dargay and Hanly, 2004;Dieleman et al, 2002;Kockelman, 1997;Krizek, 2003;McNally and Kulkarni, 1997;Schwanen et al, 2002Schwanen et al, , 2004Stead, 2001). …”
Section: Socio-economic and Demographic Differences In Travel Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…There are five dimensions contributed to the walkable environment (Mariela, 2008); feasibility, accessibility, safety, comfort and pleasurability. (Dieleman, 2002;Ball, 2000;Booth, 1997). In this research, subgroups feasibility dimension deliberate as independent variables, whilst, physical attributes categorized in accessibility, safety, comfort and pleasurability dimension deliberate as dependent variables.…”
Section: Metadata Analysismentioning
confidence: 99%